Enhanced detection of tissue auto-fluorescence by one-photon ultrafast pulsed illumination - De, A.K. (Indian Academy of Sciences, 2015)
No abstract available
Only IISER authors are available in the record.
Keywords: tissue auto-fluorescence; one-photon; ultrafast pulsed